Mortality after hospital admission for heart failure: improvement over time, equally strong in women as in men - Buddeke, J.; Valstar, G. B.; van Dis, I.; Visseren, F. L. J.; Rutten, F. H.; den Ruijter, H. M.; Vaartjes, I.; Bots, M. L. (BMC public health, 2020)
Background To assess the trend in age- and sex-stratified mortality after hospitalization for heart failure (HF) in the Netherlands. Methods Two nationwide cohorts of patients, hospitalized for new onset heart failure between 01.01.2000–31.12.2002 and between 01.01.2008–31.12.2010, were constructed by linkage of the Dutch Hospital Discharge Registry and the National Cause of Death registry. 30-day, 1-year and 5 -year overall and cause-specific mortality rates stratified by age and sex were assessed and compared over time. Results We identified 40,230 men and 41,582 women. In both cohorts, men were on average younger than women (74–75 and 78–79 years, respectively) and more often had comorbid conditions (37 and 30%, respectively). In the 2008–10 cohort, mortality rates for men were 13, 32 and 64% for respectively 30-day, 1-year and 5-year mortality and 14, 33 and 66% for women. Mortality rates increased considerably with age similarly in men and women (e.g. from 10.5% in women aged 25–54 to 46.1% in those aged 85 and older after 1 year). Between the two time periods, mortality rates dropped across all ages, equally strong in women as in men. The 1-year absolute risk of death declined by 4.0% (from 36.1 to 32.1%) in men and 3.2% (from 36.2 to 33.0%) in women. Conclusions Mortality after hospitalization for new onset HF remains high, however, both short-term and long-term survival is improving over time. This improvement was similar across all ages and equally strong in women as in men.